Council members and friends at the home of Jeannie and Hein van Wijk, during the Council Meeting at Bloemendaal. Brown sitting at the left, Bing standing at the right (1949)
Council members and friends at the home of Jeannie and Hein van Wijk, during the Council Meeting at Bloemendaal. Brown sitting at the left, Bing standing at the right.